Coping of Nursing Professionals who take care of people with Aids - an Educative-Reflective Practice - Jenifer Adriana Domingues Guedes; Miriam Süsskind Borenstein; Betina Hörner Shlindwein Meirelles (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
It's an experience report carried out with nursing professionals from a reference institution in the control of aids, which aimed to develop an educative-reflective process, based in the "Problematization" Pedagogy, about the problems that they live and face when taking care of people suffering from aids. The development of the proposal took place in the end of the second semester, in 2006, and involved 10 nursing technicians, in workshops, guided by the Arc Method of Charles Maguerez. During the workshops, the identified problems were grouped in five key points: the Particular Characteristics of the People with aids; the limited Human and Physical resources; the difficult Administrative /Organizational Questions of the institution; the Discrimination and Preconception; the negative influence of Professional life in Personal Life. The discussions carried through, showed that the professionals try to deal with their daily problems, searching for new ways which allow them to change their reality. We got to the conclusion that some of these problems are in consonance with studies previously accomplished in the same institution. Therefore, professionals together with the hospital administration, need to develop efficient coping strategies to solve the daily problems. The accomplishment of this work also opened way for the development of a new study, with a historical nature, in the institution.